2016
DOI: 10.1038/srep33563
|View full text |Cite
|
Sign up to set email alerts
|

Orange protein has a role in phytoene synthase stabilization in sweetpotato

Abstract: Carotenoids have essential roles in light-harvesting processes and protecting the photosynthetic machinery from photo-oxidative damage. Phytoene synthase (PSY) and Orange (Or) are key plant proteins for carotenoid biosynthesis and accumulation. We previously isolated the sweetpotato (Ipomoea batatas) Or gene (IbOr), which is involved in carotenoid accumulation and salt stress tolerance. The molecular mechanism underlying IbOr regulation of carotenoid accumulation was unknown. Here, we show that IbOr has an ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 46 publications
7
117
0
1
Order By: Relevance
“…To investigate the expression of IbPsbP, 1-month-old sweetpotato plants with six fully expanded leaves were subjected to various stresses [38 and 47°C (heat), 4°C (cold), 100 mM methyl viologen (MV), 10 mM H 2 O 2 , and 200 mM NaCl] (Kim et al, 2014; Park et al, 2016), and then samples were taken from the fully expanded leaves third from the top of treated plants at the indicated time. Two-month-old sweetpotato plants were used for acquisition of samples of leaves from shoot apical meristem, according to position-dependent development stage (Ji et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the expression of IbPsbP, 1-month-old sweetpotato plants with six fully expanded leaves were subjected to various stresses [38 and 47°C (heat), 4°C (cold), 100 mM methyl viologen (MV), 10 mM H 2 O 2 , and 200 mM NaCl] (Kim et al, 2014; Park et al, 2016), and then samples were taken from the fully expanded leaves third from the top of treated plants at the indicated time. Two-month-old sweetpotato plants were used for acquisition of samples of leaves from shoot apical meristem, according to position-dependent development stage (Ji et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…OR encodes a plastidial DnaJ cysteine‐rich domain‐containing protein and is highly conserved among plant species (Lu et al ., ; Tzuri et al ., ). Recent studies reveal that OR has dual roles in post‐transcriptionally regulating PSY and promoting chromoplast biogenesis for carotenoid accumulation in plants (Chayut et al ., ; Park et al ., ; Welsch et al ., ; Yuan et al ., 2015a; Zhou et al ., ). Expression of a wild‐type OR ( OR WT ) results in carotenoid accumulation in multiple plant species (Bai et al ., ; Berman et al ., ; Park et al ., ; Yuan et al ., 2015a), likely due to its role in regulating PSY activity.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue-specific expression observed between different PSYs in these species suggests a tightly regulated transcription of this step. The PSY step is also post-transcriptionally regulated by OR/OR-like proteins affecting PSY protein levels and carotenoid content in Arabidopsis and sweet potato without affecting PSY transcript levels (Zhou et al, 2015;Park et al, 2016). Recently, it has been reported that the OR protein, with the golden SNP mutation, may increase carotenoid content by negatively regulating the downstream beta-carotene hydroxylase activity in melon (Chayut et al, 2017).…”
Section: Introductionmentioning
confidence: 99%